The Effect intake of Fe tablets and Food Supplementation Biscuit on Changes of Hemoglobin level and LILA of Pregnant Women Who Have Chronic Energy Deficiency in Puskesmas Pauh Padang - Tika Dwita Adfar; Rahmita Yanti; Chynta Lara Salsabila (Universitas Darussalam Gontor, 2023)
Background: One of the problems caused by malnutrition in pregnant women is Chronic Energy Deficiency (CED). CED is a condition in which a mother experiences a chronic (chronic) lack of energy and protein. Efforts made to improve the nutrition of pregnant women with CED are by providing additional food and consuming iron (Fe) tablets. Objective: to determine the effect of giving iron tablets (fe) and food supplementation biscuits to changes in hemoglobin and LILA of pregnant women with Chronic Energy Deficiency at Pauh Padang Health Center. Methods: The study used a quasi-experimental design with a pretest-posttest two group design. The study was conducted in November 2021–January 2022. The sample size was calculated using the Lameshow formula and a sample of 52 people was obtained, with a total of 26 people in each group. The research was conducted by interview and observation. Data analysis to see the difference before and after the intervention using non parametric mann-whitney. Results: The results showed that there were differences in LILA in the control and treatment groups (P=0.000), there were differences inhemoglobininthecontrolandtreatmentgroups(p=0.001).Conclusion: thereweredifferences in hemoglobin and LILA in the control and treatment groups .